Optimization of an energy district for fuel cell electric vehicles: Cost scenarios of a real case study on a waste and recycling fleet. (8th December 2022) - Bragatto, Tommaso; Bucarelli, Marco Antonio; Carere, Federico; Cavadenti, Alessio; Santori, Francesca
Abstract: This paper analyses the planning and operation of an energy district that aims to integrate a hydrogen supply chain for feeding vehicles based on fuel cell technology. A model of an energy district and an optimization algorithm based on the economic parameters are presented and validated leveraging an existing energy district, simulating several scenarios depending on different economic conditions and technical parameters. The model of the energy district evaluates energy balances, distinguishing hydrogen and electrical energy flows; the districts can include an FCEV fleet, electrical loads, energy generators, storage system and an electrolyser for producing hydrogen from the green energy surplus produced in the district as well as drawing energy from the power distribution network. The algorithm, based on MILP, is used for optimizing the flows in the district; indeed, it evaluates all the technical and economic constraints at a certain timestamp and provides optimal scheduling of the energy units. Model and algorithm have been used to evaluate different scenarios that were identified by varying the economic parameters (i.e., prices of electrical energy and hydrogen) as well as district design (i.e., upgrading sizes of the generators and electrolysers). Energy district parameters have been identified exploiting real data collected in an existing district located in Terni (Italy) owned by the local multi-utility ASM Terni S.p.A. It already includes a fleet for waste management, PV plants, office buildings and warehouses. Through parameters combination, 1125 OPEX and 729 CAPEX simulated scenarios have been evaluated and reported; each scenario assesses the daily variation of variables' economic trends covering the timeframe from 2030 to 2050. Results of simulations highlight the most convenient economic contexts as well as the envisioned amount of expenditures for adopting FCEV in the presented district or similar ones. For the case study, the forecasted cost of the hydrogen district, including FCEVs, is fully comparable to current costs, resulting in some cases even cheaper. Highlights: Energy district model integrating hydrogen and electrical energy networks. MILP-based optimized management of hydrogen and electricity flows. Hydrogen fleet conversion analysed in real district of a waste management company. Analysis of 91, 250 technical-economical scenarios for real fleet conversion.